Методологія легалізації результатів оперативно-розшукової діяльності - Шапірко, Петро Михайлович; Шапирко, Петр Михайлович; Shapirko, Petr (Одеса : Юрид. л-ра, 2012)
The article describes the methodological and theoretical aspects of the legalization of operational and investigative information. Relationship between the concepts legalization, documentation, transformation and interpretation of the results of operational-search activities have been discussed. It is suggested that two stages of legalization operational and investigative information: primary and secondary.
Шапірко П. М. Методологія легалізації результатів оперативно-розшукової діяльності / П. М. Шапірко // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 228-236.
Keywords: легалізація; оперативно-розшукова діяльність; оперативна інформація; легализация; оперативно-розыскная деятельность; оперативная информация; legalization; operational-search activity; operational information